Comparative Clinical Trial of Mebendazole, Praziquantel and Metronidazole in Treatment of Human Giardiasis - Reza Imani (International Journal of Travel Medicine and Global Health, 2013)
Background: Giardia lamblia is a common intestinal parasite associated with social or personal problems. Giardiasis is distributed all over the world; however, the infection is more prevalent in developing countries. Metronidazole is now considered as a drug of choice for giardiasis treatment. The increasing number of reports of refractory cases as well as side effects of this drug resulted in establishment of more investigation for new compounds. Methods: In a randomized clinical trial, 90 Giardia lambilia infected cases, aged 2-30 years and each proven to be infected with Giardia lambilia by the microscopical examination of fecal sample, were randomly allocated to 3 groups. Group 1 was given metronidazole with three daily 20 mg/kg doses for 7 days. Group 2 and 3 were seperately given mebendazole and praziquantel, with single 60 mg/kg and 20 mg/kg doses, respectively, and Parasitological cure was documented when stool examination for Giardia lambilia was negative for 3 times within 7–10 days after therapy. Results: Seventeen of 30 patients treated with praziquantel, 15 of 30 patients (50%) treated with mebendazole and 28 of 30 individuals (93%) treated with metronidazole had negative stool examination results. There was not a significant difference between cure rates of praziquantel and mebendazole (P>0.05), while this difference between these two drugs and metronidazole was significant (P<0.05). Conclusion: Mebendazole and praziquantel were not as effective as metronidazole in the treatment of Giardiasis.